Pengembangan Learning Management System Berbasis Moodle pada Kompetensi Dasar Perawatan Sistem Continuously Variable Transmission - Janah, Lulu’ul; Kurniawan, Adhetya (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to develop a Learning Management System based on Moodle to improve students' learning outcomes on CVT system materials. The method used in this study is a research and development method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model and uses a one group pretest-posttest design. The research subjects are Class XI TBSM 3 students of SMK Texmaco Pemalang which totals 38 students. The results of the feasibility test from media experts got 82.5% results and the results of the feasibility test from material experts got a result of 96.25% with the category of "very feasible". The results of the analysis of t-test data obtained a significance value (2-tailed) of 0.008 (p < 0.05) which showed a significant increase in learning outcomes. The responses of educators and students were 98.75% and 95.83%, respectively, both in the "very feasible" category. These findings show that Moodle-based LMS is effective and feasible to use as a learning medium on the basic competencies of the CVT system.